Maximizing antibody production in a targeted integration host by optimization of subunit gene dosage and position. (17th February 2020) - Carver, Joe; Ng, Domingos; Zhou, Michelle; Ko, Peggy; Zhan, Dejin; Yim, Mandy; Shaw, David; Snedecor, Brad; Laird, Michael W.; Lang, Steven; Shen, Amy; Hu, Zhilan
Abstract: Historically, therapeutic protein production in Chinese hamster ovary (CHO) cells has been accomplished by random integration (RI) of expression plasmids into the host cell genome. More recently, the development of targeted integration (TI) host cells has allowed for recombination of plasmid DNA into a predetermined genomic locus, eliminating one contributor to clone‐to‐clone variability. In this study, a TI host capable of simultaneously integrating two plasmids at the same genomic site was used to assess the effect of antibody heavy chain and light chain gene dosage on antibody productivity. Our results showed that increasing antibody gene copy number can increase specific productivity, but with diminishing returns as more antibody genes are added to the same TI locus. Random integration of additional antibody DNA copies in to a targeted integration cell line showed a further increase in specific productivity, suggesting that targeting additional genomic sites for gene integration may be beneficial. Additionally, the position of antibody genes in the two plasmids was observed to have a strong effect on antibody expression level. These findings shed light on vector design to maximize production of conventional antibodies or tune expression for proper assembly of complex or bispecific antibodies in a TI system.